Trawling in the Mediterranean: An Exploration of Empirical Relations Connecting Fishing Gears, Otterboards and Propulsive Characteristics of Fishing Vessels - Sala, Antonello; Notti, Emilio; Bonanomi, Sara; Pulcinella, Jacopo; Colombelli, Alessandro (Frontiers in Marine Science, 2019)
Fishing pressure is often expressed in terms of vessel’s physical attributes, like tonnage and engine power, while a common definition of fishing capacity identifies vessel size as a convenient proxy for the size of gear used. Nevertheless, these definitions remain arguable, and the refinement of these fishing descriptors is increasingly receiving growing consideration. A stronger understanding of the relationship between the standard measures of effort and capacity and fishing mortality remains a primary objective, followed by the need to overcome a traditional approach that simply describes effort, capacity and mortality as linearly related, conferring to larger vessels a greater fishing power. In this perspective, the analysis of trawls’ technical features in relation with the size and power of the vessel might constitute an essential step. This study specifically investigated a collection of trawl gears technical specifications collected by CNR-IRBIM, Ancona. The dataset used includes records from several Mediterranean fisheries, and involves three trawling techniques, including single trawl, twin trawl and pair trawling, and diverse trawling gear categories, comprising demersal/bottom 2-panel trawls (OTB2), demersal/bottom 4-panel trawls (OTB4), pelagic 4-panel trawls (PTM4), semi-pelagic 2-panel trawls (OTM2), semi-pelagic 4-panel trawls (OTM4), and Mediterranean bottom beam trawl (TBB). We analyzed and described the relationships between vessels’ technical features (LOA, towing force, engine power), some among the main trawl-metrics (headline length, footrope length, trawl length, square width; fishing circle) and otterboard’s technical features (height, width, projected area) in the attempt to enhance fishing capacity definition through the inclusion of the fishing gear deployed. Self-Organizing maps were used to explore the empirical relationships among different parts of the fishing trawl gears, as well as between some of these parts and the otterboard size and the engine power of the vessel.